PENERAPAN METODE S ELF HEALING : RELAKSASI BENSON SEBAGAI STRATEGI PENURUNAN TINGKAT STRES KERJA PADA PERAWAT IGD RSUP. PROF. DR. R. D. KANDOU MANADO - Kristiana Priskila Walintukan; Hendro Bidjuni; Andi Buanasari (JURNAL KEPERAWATAN, 2022)
Background : Stress working on nurses gives influence on mutual service, health mental and physical even quality of work. Benson relaxation is a form of self-healing that can create a calm and comfortable feeling. The purpose of this study was to determine the effectiveness of the application of the self-healing method: Benson relaxation as a strategy to reduce work stress levels in emergency room nurses at RSUP. Prof. Dr. R.D. Kandou Manado. This research method uses a quasi-experimental research design with a pretest-posttest research design with control design. The sample amounted to 38 respondents, each of which was 19 respondents for the experimental group and the control group. The instrument used is the ENSS questionnaire to measure the level of work stress. The results of the study using the Paired Sample T Test in the experimental group p value (0.000) < (0.05), so that H0 is rejected, which means that there is a difference between the pretest and posttest. . In the control group p value (0.075)> (0.05), so there is no difference between the pretest and posttest. While the results of statistical tests using the Independent T test obtained p-value (0.002) < (0.05) meaning that there is a significant difference between the work stress of nurses in the experimental group and the control group. The conclusion is that there is a significant difference after the intervention on the work stress of nurses. Benson relaxation therapy is recommended as an alternative to non-pharmacological therapy in dealing with nurses' work stress.